ENHANCING ENGLISH COMMUNICATION SKILLS THROUGH MEDIA PRODUCTION - Pramana, Aditya Surya; Husen, Unais; Sari, Ikmala (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2025)
This program at Radio Bhasa FM Situbondo aimed to enhance English-speaking skills through practical experience in media production and community engagement. Activities included news production, podcast discussions, educational content creation, and a community-based mosque cleaning program. The method involved researching topics, scriptwriting, recording, editing, and broadcasting content on radio and social media platforms. These programs improved students' communication skills while promoting social awareness. The program demonstrated the effectiveness of media as an educational tool and fostered confidence in public speaking. The project’s success highlights the importance of integrating language learning with real-world application.